Internet governance is what global stakeholders make of it: A tripolar approach - Pigatto, Jaqueline Trevisan [UNESP]; Datysgeld, Mark W.; da Silva, Laura Gabrieli Pereira [UNESP] (FapUNIFESP (SciELO), 2021)
This paper seeks to identify the configuration of Internet governance in late 2021, focused on the dispute over institutional representation and legitimacy in which major regional powers find themselves. The United States, the European Union, and China compose a tripolar arrangement, each advancing a distinct mode of governance with unique characteristics that we strive to analyze here.
Keywords: Digital sovereignty; Internet governance; Multistakeholder model; Regulation